Factors influencing primary stability of dental implants assessed with resonance frequency analysis: an in vitro study - Rodrigues, Catarina Gonçalves (2017)
Tese de mestrado, Medicina Dentária, Universidade de Lisboa, Faculdade de Medicina Dentária, 2016